Elemen Sinematografi Dalam Iklan Toyota Gazoo Racing Versi Wild Moment - Putu Raka Setya Putra; Chris Chalik; Ahmad Riyadi Swandhani (MAVIS : Jurnal Desain Komunikasi Visual, 2025)
Toyota Gazoo Racing is one of Toyota’s racing divisions that has made a significant contribution to the development of automotive technology. This initiative originated from the vision of Toyota’s founder, Kiichiro Toyoda, who believed that car racing is not merely a form of entertainment but an essential means to test vehicle performance under extreme conditions while simultaneously discovering new innovations to deliver the best products for consumers. Based on this perspective, the present study aims to analyze the application of cinematographic elements in Toyota Gazoo Racing advertisements and their impact on brand visual communication strategies. This research employs a descriptive qualitative method with a case study approach. Data were collected through observations of cinematographic elements in Toyota Gazoo Racing advertisements, which were then mapped and validated with relevant literature on cinematography in advertising. The findings indicate that cinematography plays a crucial role in constructing visual narratives that strengthen Toyota’s brand image in terms of performance, endurance, and innovation. These results are expected to serve as a reference for designing cinematographic strategies in future automotive advertising campaigns.